Inter-relações entre necessidade de hedging, assimetria entre direitos de controle e propriedade, políticas de caixa e dívida em condições de restrição financeira - Portal, Márcio Telles (Universidade do Vale do Rio do Sinos, 2010)
This study investigated If Brazilian firms between 1995 and 2005 coordinate policies of cash and debt for the purpose of hedging in condition of financial constraint. And as the asymmetry of rights of control and ownership act on substitution effect between cash and debt in condition of financial constraint and hedging need. The results indicate the inexistence of a hedging component using both cash and debt policies. It was noted that: the incentive to save cash is greater when less difference between rights of control and ownership (wedge); the group of companies with low wedge is the group with the highest average concentration of control; that the positive cash flow sensitivity of debt only in the state of high hedging need and is strongly associated with the occurrence of high concentration of ownership and financial constraint; companies with low hedging need and high concentration of ownership present cash flow sensitivity of cash regardless of the state of financial constraint. The results are unawar
Keywords: estrutura de controle; estrutura de propriedade; hedging; política de caixa; política de dívida; restrição financeira; cash policy; hedging policy; ownership of structure; policy debt; structure of control; financial constraint; Ciências Sociais Aplicadas